Effects of Sublethal Zn++ and Cd++ Concentrations on Filtration Rate, Absorption Efficiency and Scope for Growth in Donax trunculus (Bivalvia; Donacidae) - Lya Neuberger-Cywiak; Y. Achituv; E. M. Garcia (Bulletin of Environmental Contamination and Toxicology, 2007)

Differential Gene Expression in Symbiodinium microadriaticum Clade B Following Stress - S. Karako-Lampert; G. Hershkovits; N. Stambler; N. Simon-Blecher; Y. Achituv; Z. Dubinsky; D. J. Katcoff (Marine Biotechnology, 2006)

Fine structure of naive and allogeneic challenged ampullae in Botrylloides subpopulation I from the Mediterranean coast of Israel - N. Simon-Blecher; J. Hanania; Y. Achituv; B. Rinkevich (Marine Biology, 2006)

Sublethal Effects of Zn++ and Cd++ on Respiration Rate, Ammonia Excretion, and O:N Ratio of Donax trunculus (Bivalvia; Donacidae) - L. Neuberger-Cywiak; Y. Achituv; E. M. Garcia (Bulletin of Environmental Contamination and Toxicology, 2005)

Effects of Zinc and Cadmium on the Burrowing Behavior, LC 50 , and LT 50 on Donax trunculus Linnaeus (Bivalvia-Donacidae) - L. Neuberger-Cywiak; Y. Achituv; E. M. Garcia (Bulletin of Environmental Contamination and Toxicology, 2003)

Speciation and the establishment of zonation in an intertidal barnacle: specific settlement vs. selection* - L. Appelbaum; Y. Achituv; O. Mokady (Molecular Ecology, 2002)
The tropical barnacle Tetraclita forms a belt on hard substrates in the intertidal zone of the Red Sea. Based on morphological data, three distinct species were suggested to exist, occupying different vertical levels — T. barnesorum, T. rufotincta and T. achituvi . In this study we used molecular (12 S mitochondrial ribosomal DNA) and ecological data to examine whether this morphological variability reflects genetic differences, or is a result of environmental factors. Adults and spats, collected from settlement plates, were censused and screened genotypically using single strand conformation polymorphism (SSCP) analysis, and settlement dynamics was recorded. We provide evidence for the existence of only two distinct species, and point out both phenotypic plasticity and convergence within and between the proposed species. Cyprids of T. achituvi settle specifically at the lower part of the Tetraclita belt, and feature one phenotype. In contrast, T. rufotincta , occupying the upper and middle portions of the Tetraclita belt, settles throughout the range, shows phenotypic plasticity (three variants), and presumably undergoes selection at the lower part. Thus, the vertical zonation of Tetraclita is produced by the combination of pre‐settlement and post‐settlement factors, in T. achituvi and T. rufotincta , respectively. The examined system may offer a model in which to study the mechanisms underlying sympatric speciation.

Pit structure and trophic relationship of the coral pit crab Cryptochirus coralliodytes - N. Simon-Blecher; A. Chemedanov; N. Eden; Y. Achituv (Marine Biology, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Stable carbon isotope ratios in Red Sea barnacles (Cirripedia) as an indicator of their food source - I. Brickner; J. Erez; Y. Achituv (Marine Biology, 1997)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)